Optimizing Indonesia's Digital Diplomacy through a Multitrack Peace Building Approach: A Case Study of the Palestine-Israel Conflict - M. Yusuf Samad; Nour Zattullah; Friztky Prawita Abdullah; Zestadianna Adzel; Diah Ayu Permatasari; Pratama Dahlian Persadha; Taryana Brata (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2023)
Digital diplomacy is used as an instrument to convey a country's foreign policy and national interests in responding to situations that occur globally. Indonesia through President Joko Widodo has implemented this to address the conflict between Israel and Palestine. However, President Jokowi's digital diplomacy through the official Twitter account (X)  has not been optimal when viewed from the multitrack peace-building approach perspective. This study aims to optimize the implementation of Indonesia's digital diplomacy towards the Israeli-Palestinian conflict through a multitrack peace-building approach. This research uses a qualitative method with a case study of President Jokowi's official Twitter account uploads related to the Israel-Palestine conflict. The results showed that Indonesia's digital diplomacy through President Jokowi's official Twitter account can be optimized through the involvement of middle-level leadership, especially the religion-based peace-building approach in the form of interacting with the Chairman of the Indonesian Ulema Council for Da'wah and Ukhuwah as well as Rais Syuriyah of the Nahdlatul Ulama Executive Board, M. Cholil Nafis (@cholilnafis) and General Secretary of the Muhammadiyah Central Board Abdul Mu'ti accounts. In addition, at the grassroots level, leadership can be optimized by involving the Chief Trustee of the Nusantara Palestina Center, Abdillah Onim account and if possible, also interacting with the Nusantara Palestina Center organization account considering that both of them continuously inform the latest conditions in Palestine.